Housing and transport in Malaysia: a fundamental combination in determining affordability - Raja Ariffin, Raja Noriza; Zahari, Rustam Khairi; Makmor, Tumin (AENSI Journals, 2015)
Malaysia is undergoing significant changes through rapid economic development. Growing urban population led to challenges confronting the housing and transportation sectors, affecting affordability. Objectives: This literature review on housing and transport was conducted to explore Malaysia’s housing and transport affordability issues. This study also provides an overview of housing policies in relation to housing and transport affordability. Results: Increased urban population; housing/transportation connectivity; affordable-accessible housing; and housing price/income mismatch were identified as key challenges of Malaysia’s housing and transport affordability. Integrating housing location and public transport networks not only improves regional accessibility, but also reduces traffic congestion and rejuvenates neighborhoods. Conclusion: A new or improved sustainable public transport system can ultimately boost the growth of the local and regional economy.